Easy and One‐Step Synthesis of Ir Single Atom Doped PPy Nanoparticles for Highly Active N‐Alkylation Reaction. Issue 7 (19th January 2021) - Iuliano, Mariagrazia; Sarno, Maria; Cirillo, Claudia; Ponticorvo, Eleonora; De Pasquale, Salvatore
Abstract: Single atoms are nowadays considered new catalysts offering a lot of advantages such as reduced cost and use of noble metals. Here, we report the catalytic activity towards N‐alkylation reactions of single atoms (SACs) of iridium doped polypyrrole (Ir−PPy nanoparticles). The new nanocatalyst exhibits excellent behavior due to the combination of highly active SACs catalyst and the organic conductive support providing strong binding of single atoms and thus improved reusability and easiness to handle. In the presence of a low amount of Ir and of a suitable base, excellent activity (yield >99 %) and selectivity (>99 %) were obtained. In the optimized Ir condition (3 wt.% of Ir) an aniline conversion of about 99 %, with excellent selectivity, just after 600 min, was obtained. Recyclability tests show that the catalyst can be successfully recycled six times without significant catalyst activity loss. Abstract : N‐alkylation was studied in detail to identify the optimal conditions to obtain high yields and selectivity. The study was extended to the analysis of different reagents and the effect of reuse cycles. The new nanocatalyst based on the presence of Ir SACs and a conductive support of PPy was extensively characterized also during use and its reaction mechanism was hypothesized.